Inequality aversion in income, health, and income-related health - Hurley, J; Mentzakis, E; Walli-Attaei, M (Elsevier, 2020)
Based on a survey of a sample of the general public, we estimate inequality aversion across income, health, and bivariate income-health. Inequality aversion is domain specific: mean inequality aversion is greater for income than for health, but the underlying distributions of aversion attitudes differ, with a highly bi-modal distribution of inequality-aversion values for health in which nearly half the participants display very low aversion and nearly half display very high aversion. Aversion to income-related health inequality is greater than that to income or health alone. Consistent with previous literature, we find only weak associations between aversion attitudes and individual characteristics. The magnitude of the estimates implies potentially large gains in welfare from reducing inequality in these domains.